Effects of sevoflurane and propofol for elderly patients: A systematic review and meta-analysis - Qi Wang; Jing Luan; Wenli Yu (Journal of Research in Medical Sciences)
Background: To evaluate the safety of propofol and sevoflurane for general anesthesia in elderly. Materials and Methods: All studies on sevoflurane, propofol, and hyperamylasemia from the establishment of Embase, Ovid, Cochrane Library, and Google Scholar from database establishment to December 2024 were searched. Literatures were screened, and data were extracted on the grounds of inclusion and exclusion criteria. Review Manager (RevMan) (Version 5.4. The Cochrane Collaboration.) was used for statistical analysis. Outcomes assessed included time to spontaneous eye opening, extubation time, incidence rate of postoperative cognitive dysfunction (POCD), postoperative delirium, agitation, nausea and vomiting. Results: Fourteen trials were identified and included in this meta-analysis. The results showed no significant difference in time to spontaneous eye opening (P = 0.54), the incidence of POCD (P = 0.07), postoperative delirium (P = 0.37), and postoperative nausea and vomiting (P = 0.8) between the sevoflurane and propofol groups. Compared with propofol groups, extubation time (P < 0.0001) was significantly shortened by sevoflurane groups. Conversely, compared with sevoflurane, the incidence of postoperative agitation in the propofol group was significantly reduced (P = 0.04). Conclusion: There was no difference in time to spontaneous eye-opening, the incidence of POCD, postoperative delirium, postoperative nausea, and vomiting between the sevoflurane and propofol groups. However, compared with propofol, sevoflurane can significantly shorten intubation time. The incidence of postoperative agitation (P = 0.04) was significantly lower in the propofol group compared with sevoflurane.